STUDYING MORPHOLOGY ON A SYNTACTIC BASIS IN THE PROCESS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE - Nodia, Tea; Khatiashvili, Khatia ("Intercultural Dialogues" Transactions, 2025)
When studying any language, not only dictionaries describing vocabulary are necessary, but also grammar as a set of rules of this language, allowing you to understand and construct sentences and texts in this language. A person studying any language constantly looks into grammar, mastering the rules of sentence construction in a particular language. These rules are presented as multi-step tasks associated either with recognizing a form and determining its meaning in context, or with creating such forms that would accurately express its intent and not violate the rules of sentence construction. The question of how to use grammar and in what dose has always caused controversy among teachers of the Russian language. One thing was certain: the combination of lexical and grammatical material creates the basis for studying the language. We can agree that the methodological skill of the teacher who has chosen a specific path of combining these two components is important here.